Penerapan Metode Numerik dalam Penyelesaian Persamaan Diferensial - Tsuwaibatul Aslamiyah Lubis (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This research discusses the application of numerical methods in solving differential equations that often appear in various fields of science, such as physics, engineering and economics. The methods used include the Euler method, the Runge-Kutta method, and the finite difference method. The research results show that the fourth order Runge-Kutta method provides a higher level of accuracy than the Euler method in solving first order differential equations. In addition, the finite difference approach provides stable solutions to partial differential equations. This study confirms the importance of numerical methods in the analysis and solving of complex mathematical problems.